Social capital and social ties in organisations: a case study of two voluntary sports clubs. Issue 9 (15th November 2019) - Tacon, Richard
Abstract : Purpose: If social capital is understood as the ability to access resources through social ties, it is clearly important to understand how people form social ties and what types of ties they form. Research has sought to do this, but it has seldom directly examined how organisations shape these processes and outcomes. The paper aims to discuss this issue. Design/methodology/approach: In-depth, comparative case study research was conducted at two voluntary sport organisations in the UK, involving 23 in-depth interviews and participant observation over a 15-month period. Findings: The case studies showed how key organisational practices structured, in meaningful ways, people's opportunities for interaction and the nature of that interaction, shaping the ways in which they formed ties and exchanged resources. The organisations fostered the formation of both strong and weak ties, but also "compartmentally intimate" ties. Research limitations/implications: The research challenges individualistic, rational choice accounts of tie formation, highlighting the role of organisations as brokers. In addition, interviewees' accounts challenge well-accepted distinctions between strong and weak ties, by demonstrating the importance of ongoing, context-specific interaction. Originality/value: This research offers a rare, direct insight into the role of organisations in shaping people's ongoing social relationships. In doing so, it problematises existing conceptualisations of social capital and social ties and highlights an alternative, organisationally embedded, process-based perspective on social capital.